Oxidative DNA damage and total antioxidant status in rats during experimental gram-negative sepsis - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2008)
Sepsis and septic shock remains as leading cause of death in adult intensive care units. It is widely accepted that gram-negative bacteria and their endotoxins cause sepsis and septic shock, predominantly. Enhanced generation of reactive oxygen species may be responsible for tissue injury in septic shock and endotoxemia. The aim of this study was to assess oxidative DNA damage and the total antioxidant status (TAS) in peripheral lymphocytes of rats during different intraperitoneal gram-negative sepsis stages. Adult male Sprague-Dawley rats were divided randomly into four groups. Control group was intraperitoneally inoculated with 2 ml, of pyrogene-free saline (Group I, n = 6), and the other rats received an intraperitoneal inoculum with 2 ml, of saline containing 2 x 10(8) CFU of Escherichia coli. The animals were killed at time zero (Group 1, n = 6), at 6th (Group 11, n = 7), 12th (Group M, n = 7), and 24th (Group IV, n = 7) hour after the E. coli inoculation. Oxidative DNA damage in peripheral lymphocytes of rats was evaluated by modified comet assay (single-cell gel electrophoresis). Formamido-pyrimidine DNA glycosylase (Fpg) and Endonuclease III (Endo III) were used to detect oxidized purines and pyrimidines, respectively. Total antioxidant quantification was carried out using ABTS+ (2,2'-Azino-di-[3 ethyl-benzthiazoline sulphonate]) radical formation kinetics (Randox kit) in serum samples. Significant elevations of basal levels of strand breaks (SB) in Group IV were observed as compared with Group I, II, and III. There was a significant increase in Fpg sites in Group III as compared with Group I and II. However, there was no significant difference in terms of Endo III sites in any of the groups. Although the TAS was decreased with the stages of sepsis, this moderate decrease was significant in only Group IV as compared with Group I. There was no statistically significant correlation between DNA damage and TAS for any of the groups.
Keywords: modified comet assay; oxidative DNA damage; sepsis; total antioxidant status; NITRIC-OXIDE SYNTHASE; SEPTIC SHOCK; EXPERIMENTAL-MODELS; ORGAN DYSFUNCTION; ENDOTOXIC-SHOCK; CELL-DEATH; APOPTOSIS; FRAGMENTATION; PATHOGENESIS; INFLAMMATION